Imaging spectrum of extrapulmonary manifestations of COVID-19 infection- a multi-centre descriptive study from Southern India - Mahalingam, Harshavardhan; Murali, Lokesh; Govisetty, Ashwini; Aiyappan, Senthil Kumar; Ramakrishnan, Karthik Krishna; Rajan, Seena Cheppala; Rangasami, Rajeswaran; Shanmugham, Vinayagam (International Journal of Research in Medical Sciences, 2022)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) is the causative agent for coronavirus disease 2019 (COVID-19) pandemic. While the primary organ of involvement in this disease is the lung, multiple other organ systems can be involved either due to direct viral cytopathic effects or due to thrombo-inflammation and immune system dysregulation. In this study we describe the spectrum of extrapulmonary imaging findings encountered in our patients with COVID-19. Methods: This was a retrospective observational study conducted in three tertiary care hospitals in the city of Chennai in southern India. All cross-sectional imaging studies (other than lung imaging studies) performed in patients who had proven COVID-19 infection by RT-PCR testing during the period from April 2020 to March 2021 were included as part of the study. Extrapulmonary findings in these imaging studies were recorded and collated system-wise. Results: A total of 96 non-lung imaging studies were performed in patients who had RT-PCR positivity for COVID-19 infection. Among these a total of 30 studies had extrapulmonary imaging findings. Vascular involvement was seen in 14 patients, central nervous system involvement in 13 patients, abdomen involvement in 2 patients, and cardiac involvement in 1 patient. Vascular manifestations included arterial and venous thrombosis. Neurological manifestations included stroke, encephalitis and demyelination. Abdominal manifestations included enteritis and acute kidney injury. Cardiac manifestation was in form of myocarditis. Conclusions: Extrapulmonary imaging findings in COVID-19 are uncommon but not rare. Multisystem thrombotic manifestations and central nervous system involvement account for majority of extrapulmonary imaging findings in COVID-19.